Transmission line trip faults under extreme snow and ice conditions: a case study - Guojun Zhang (Energy Informatics)
Abstract Extreme weather events, particularly snow and ice storms, present significant threats to the stability and reliability of high-voltage transmission lines, leading to substantial disruptions in power supply. This study delves into the causes and consequences of transmission line trip faults that occur under severe winter conditions, with a focused case study in Inner Mongolia—an area frequently impacted by snow and ice hazards. By systematically analyzing field data collected during critical periods of ice accumulation, this research identifies and examines key factors contributing to faults, such as conductor galloping, insulator degradation, and structural fatigue. These issues are often exacerbated by prolonged exposure to low temperatures and high wind speeds, which further compromise the integrity of transmission infrastructure. In addition to field observations, comprehensive testing of the affected insulators and components reveals mechanical and electrical vulnerabilities that play a significant role in the occurrence of trip faults. To combat these challenges, the paper proposes a series of mitigation and prevention strategies. These include enhancing design specifications to ensure resilience against increased ice and wind loads, deploying real-time monitoring systems capable of detecting early indicators of conductor galloping and ice accumulation, and employing advanced de-icing technologies to reduce the risk of ice-related failures. Moreover, the integration of unmanned aerial vehicles (UAVs) and artificial intelligence (AI)-based fault detection tools presents promising opportunities for improving remote monitoring capabilities and enabling proactive maintenance interventions. By leveraging these innovative technologies, the resilience of transmission lines in harsh climates can be significantly enhanced. The findings of this study not only provide a comprehensive framework for minimizing the impact of extreme weather on transmission infrastructure but also contribute valuable insights toward fostering a more reliable and resilient power grid capable of withstanding the challenges posed by an increasingly volatile climate.